Biosurfactants as templates to inspire new environmental and health applications - Vigil, Toriana N.; Felton, Samantha M.; Fahy, William E.; Kinkeade, Mason A.; Visek, Alexandra M.; Janiga, Abigail R.; Jacob, Sarah G.; Berger, Bryan W. (Frontiers in Synthetic Biology, 2024)
Life exists at an interface. One of the key characteristics of biological cells is compartmentalization, which is facilitated by lipids that create a water-impenetrable barrier to control transport of materials across the hydrophilic-hydrophobic interface. Microbial systems utilize a rich diversity of surfactants beyond lipids to adapt to an environmental niche, modify the properties of an interface, facilitate solubilization of nutrients for metabolism and as antimicrobials. As such, they are a fascinating class of biomolecules to study in terms of how effectiveness in an application or niche environment depends on sequence, structure and chemical properties. Moreover, there is increasing appreciation of the negative health and environmental impacts petrochemical-based surfactants can have, such as soil erosion and toxicity to plants and aquatic life, as well as the carbon footprint and associated greenhouse gas emissions associated with petrochemical surfactant manufacturing. In this review, we discuss the properties of biosurfactants and applications, and highlight key glycolipid-, protein-and peptide-based surfactants described in literature as examples of biosurfactants with unique potential and applications.As society looks towards the transition to a circular bioeconomy, we are excited by the potential of synthetic biology to develop new materials such as biosurfactants to facilitate this important transition.